Computer Integration and Catastrophic Process Failure in Flexible Production - Upton, D; McAfee, A (1998)
This paper empirically investigates the effect of advanced manufacturing technology on process stability during flexible production in a process industry. A sample of 61 North American fine paper plants is used to examine the relationship between the level of automation installed for controlling changes between paper grades and the incidence of paper web breaks. These web breaks are catastrophic failures; they require the entire plant to be stopped, reinitialized, and restarted. Because a large fraction of breaks occurs shortly after changeovers, they are an important determinant of the aspect of plant flexibility, called mobility, or the ability to move between products with only small penalties. In an attempt to ensure stable and mobile production, many plants have implemented changeover automation. We find, however, that higher levels of this automation are significantly associated with higher rates of catastrophic failure among the plants studied. We suggest that this finding becomes less paradoxical when considered in light of a recent stream of research on advanced manufacturing technologies, loosely called the usability perspective. According to this perspective, automation designed and implemented with the narrow, technical goal of replacing human operators or removing their discretion over a production process is misguided, especially in environments in which requirements are changing rapidly.